The association of individual cognition and social environment of smoking with autonomy over tobacco: A survey from rural China - Jiaoyan Li; Yimei Zhu; Zhihong Zhang; Deyu Cai; Huinan Han; Jing Liang; Fang Wang; Beizhu Ye; Yuan Liang (Tobacco Induced Diseases)
Introduction This study explores the association of individual cognition and social environment of smoking with autonomy over tobacco, providing evidence and insights to help smokers effectively prevent and reduce tobacco dependence.